Phase II Study of Copanlisib in Patients With Tumors With PIK3CA Mutations: Results From the NCI-MATCH ECOG-ACRIN Trial (EAY131) Subprotocol Z1F. Issue 14 (10th May 2022) - Damodaran, Senthil; Zhao, Fengmin; Deming, Dustin A.; Mitchell, Edith P.; Wright, John J.; Gray, Robert J.; Wang, Victoria; McShane, Lisa M.; Rubinstein, Larry V.; Patton, David R.; Williams, P. Mickey; Hamilton, Stanley R.; et al.
Abstract : PURPOSE: Activating mutations in PIK3CA are observed across multiple tumor types. The NCI-MATCH (EAY131) is a tumor-agnostic platform trial that enrolls patients to targeted therapies on the basis of matching genomic alterations. Arm Z1F evaluated copanlisib, an α and δ isoform–specific phosphoinositide 3-kinase (PI3K) inhibitor, in patients with PIK3CA mutations (with or without PTEN loss). PATIENTS AND METHODS: Patients received copanlisib (60 mg intravenous) once weekly on days 1, 8, and 15 in 28-day cycles until progression or toxicity. Patients with KRAS mutations, human epidermal growth factor receptor 2–positive breast cancers, and lymphomas were excluded. The primary end point was centrally assessed objective response rate (ORR); secondary end points included progression-free survival, 6-month progression-free survival, and overall survival. RESULTS: Thirty-five patients were enrolled, and 25 patients were included in the primary efficacy analysis as prespecified in the Protocol. Multiple histologies were enrolled, with gynecologic (n = 6) and gastrointestinal (n = 6) being the most common. Sixty-eight percent of patients had ≥ 3 lines of prior therapy. The ORR was 16% (4 of 25, 90% CI, 6 to 33) with P = .0341 against a null rate of 5%. The most common reason for protocol discontinuation was disease progression (n = 17, 68%). Grade 3/4 toxicities observed were consistent with reported toxicities for PI3K pathway inhibition. Sixteen patients (53%) had grade 3 toxicities, and one patient (3%) had grade 4 toxicity (CTCAE v5.0). Most common toxicities include hyperglycemia (n = 19), fatigue (n = 12), diarrhea (n = 11), hypertension (n = 10), and nausea (n = 10). CONCLUSION: The study met its primary end point with an ORR of 16% ( P = .0341) with copanlisib showing clinical activity in select tumors with PIK3CA mutation in the refractory setting. Abstract :